Perkembangan Kemampuan Linguistik Anak Usia Dini: Kajian Pemerolehan Bahasa Pertama (First Language Acquisition) dalam Konteks Bilingual FLA - Ibrahim, Linda Fitri (Malewa: Journal of Multidisciplinary Educational Research, 2025)
First language acquisition is the process by which someone acquires their first language. Acquisition refers to linguistic ability in a natural, unconscious manner and focusing on linguistic forms. Children aged 0-5 years begin to use language and require assistance and stimulation from parents and their surroundings to help develop their language skills. The purpose of this research is to describe first language acquisition in children in developing linguistic abilities in morphology and syntax within the context of simultaneous bilingual first language acquisition (Bilingual FLA) of Indonesian (B1) and Gayo (B2). The type of this research is descriptive qualitative. The data sources in this research are 2 (two) children aged 2 to 3 years. Data collection techniques were carried out through observation and documentation. The research results can be classified into a) Morphological development in 2-year-old children; b) Syntactic development in 2-year-old children; c) Morphological development in 3-year-old children; d) Syntactic development in 3-year-old children. The development of these abilities is marked by an increase in vocabulary, the ability to form simple sentences, and the mastery of several language functions in children aged 2 and 3 years.